Direct observation of aqueous secondary organic aerosol from biomass-burning emissions - Gilardoni, Stefania; Massoli, Paola; Paglione, Marco; Giulianelli, Lara; Carbone, Claudio; Rinaldi, Matteo; Decesari, Stefano; Sandrini, Silvia; Costabile, Francesca; Gobbi, Gian Paolo; Pietrogrande, Maria Chiara; Visentin, Marco; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
The mechanisms leading to the formation of secondary organic aerosol (SOA) are an important subject of ongoing research for both air quality and climate. Recent laboratory experiments suggest that reactions taking place in the atmospheric liquid phase represent a potentially significant source of SOA mass. Here, we report direct ambient observations of SOA mass formation from processing of biomass-burning emissions in the aqueous phase. Aqueous SOA (aqSOA) formation is observed both in fog water and in wet aerosol. The aqSOA from biomass burning contributes to the "brown" carbon (BrC) budget and exhibits light absorption wavelength dependence close to the upper bound of the values observed in laboratory experiments for fresh and processed biomass-burning emissions. We estimate that the aqSOA from residential wood combustion can account for up to 0.1-0.5 Tg of organic aerosol (OA) per y in Europe, equivalent to 4-20% of the total OA emissions. Our findings highlight the importance of aqSOA from anthropogenic emissions on air quality and climate.